DEVELOPMENT OF UNMANNED AERIAL VEHICLE (UAV) IMAGE PROCESSING TECHNIQUES FOR MAPPING CORAL REEF - CHONG WEI SHENG (UNIVERSITI MALAYSIA TERENGGANU, 2022)
Coral reefs in Malaysian waters were once abundant, but they are now sparse or disrupted due to natural and anthropogenic threats. Reef scientists and managers need a quick and cost-effective solution for assessing and monitoring coral reef habitat degradation. Previous research has shown that advancement in UAV (Unmanned Aerial Vehicle) remote sensing technology, specifically the usage of multispectral UAV imagery, is known for coral reef mapping. This research aims to enhance coral reef mapping capability in coral-dominated Pulau Bidong by combining multispectral UAV imagery and suitable image processing techniques for heterogeneous coral reef ecosystems (Terengganu, Peninsular Malaysia). The UAV-based coral reef mapping method divided into four significant steps: (1) UAV data acquisition missions; (2) image pre-processing and interpretation using remote sensing techniques; (3) coral reef map production; and (4) map product accuracies assessment and validation. On the other hand, sun glint can severely hinder UAV missions, making it challenging to obtain precise coral reef extent and distribution information from sun glint-affected imagery. This thesis refined and analysed sun glint correction methods on UAV imagery as a technical enhancement for coral reef mapping image processing.